CONSTITUTIONAL VALUES AND SOCIAL JUSTICE IN INDIA - Aadil Ahmad Shairgojri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
In the present study, we employ a comprehensive approach to investigate the intersection of constitutional values and social justice in India. The study involves a nationwide quantitative survey, as well as qualitative interviews and focus group discussions. We carry out statistical analysis of survey data and conduct thematic analysis of qualitative data to examine the alignment of constitutional principles with the pursuit of social justice in the country. We conduct a thorough review and analysis of relevant constitutional provisions, judicial decisions, and policies to assess their impact on promoting social justice. Comparative analysis with international practices provides insights into potential areas for improvement. The research results in policy recommendations aimed at strengthening the connection between constitutional values and social justice in India. Throughout the study, we strictly adhere to ethical guidelines to ensure the protection of participants' rights and confidentiality. We disseminate the findings and recommendations to relevant stakeholders, contributing to ongoing discussions on social justice reform in India.